The magnificent Ambersons [videorecording (DVD)] - Cotten, Joseph, 1905-1994; Baxter, Anne; Moorehead, Agnes, 1900-1974; Tarkington, Booth, 1869-1946 (Criterion collection, 2018)
A brilliant, moving portrayal of an aristocratic American family in what many critics consider a masterpiece equal to Citizen Kane. Based on a novel by Booth Tarkington, the drama begins in the 1870s when the Amberson family is at the height of its wealth and prestige. But the day arrives when all the Ambersons are stunned by the truth of their financial ruin.